Simplify each of the following. Assume a, x and y are not zero. $\displaystyle \frac {8x}{24}=$ $\displaystyle \frac {15a^2}{25a}=$ $\displaystyle \frac {10^2}{10^3}=$ $\displaystyle \frac {-x^2y}{(-x^2)^2y^2}=$
Follow Math Help Forum on Facebook and Google+
Originally Posted by elliotfsl Simplify each of the following. Assume a, x and y are not zero. $\displaystyle \frac {8x}{24}=$ $\displaystyle \frac {15a^2}{25a}=$ $\displaystyle \frac {10^2}{10^3}=$ $\displaystyle \frac {-x^2y}{(-x^2)^2y^2}=$ $\displaystyle 1) \frac{8(x)}{8(3)} = \frac{x}{3}$ $\displaystyle 2) \frac{5a(3a)}{5a(5)} = \frac{3a}{5}$ $\displaystyle 3) \frac{10^2(1)}{10^2(10)} = \frac{1}{10}$ $\displaystyle 4) \frac{(-x^2) y}{(-x^2)^2 y^2} = \frac{1}{(-x^2) y}$
View Tag Cloud